The Effect of Using Iron Ore Sediment Waste as a Substitute for Fine Aggregate on Concrete Characteristics - Idrus, Muhammad; Gusty, Sri; Chaerul, Muhammad (ASTONJADRO, 2025)
Concrete is the main material in infrastructure development throughout the world. Its high mechanical strength and durability make it the main choice in various construction applications, from roads to high-rise buildings. However, behind its benefits, concrete production also triggers serious environmental problems. Natural aggregates such as river sand are used on a large scale. One of the materials that can be used as a substitute for fine aggregate is iron ore sediment waste. This study aimed to analyze the characteristics of fresh concrete using iron ore sediment waste as a substitute for fine aggregate using experimental methods. This study aimed to analyze the characteristics of fresh concrete using iron ore sediment waste as a substitute for fine aggregate using experimental methods. From the results of testing iron ore sediment waste aggregates such as the characteristics of iron ore sediment waste aggregates, 71% met the requirements as a material for making concrete, except for the mud content and organic content so special treatment is needed, namely the iron ore sediment waste material must be washed clean before use. The characteristics of iron ore sediment waste concrete have requirements from the average slump test value of 9 cm and there is no segregation and bleeding in the fresh concrete mixture.